Anti‐inflammatory and bactericidal effect of keratin/harmaline/ginkgo biloba electrospun nano fibres as band aid - Matine Monavari; Salar Zohoori; Abolfazl Davodiroknabadi (Micro & Nano Letters, 2022)
Abstract This study represents the extraction of keratin from hedgehogs spines doped with Harmaline and Ginkgo Biloba, and electrospun on the surface of cotton fabric (animal rights laws were performed). The field emission scanning electron microscopy (FESEM) was used to investigate the morphology of produced keratin Harmaline Ginkgo Biloba (KHG). The thermogravimetric analysis (TGA) shows the weight loss of samples in different temperatures. The aim and goal of producing KHG on the cotton fabric surface was to use as band aid; therefore, the bactericidal and anti‐inflammatory of samples were investigated. The results show that the KHG band aid has about 95% bactericidal properties against both gram‐positive and gram‐negative bacteria (Bacillus cereus and Escherichia coli). On the other hand, the results of oedema reduction on rats indicate that KHG band aid has good anti‐inflammatory property, which is near to the indomethacin. Furthermore, the MTT (3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide) analyses of KHG band aid and its cell viability demonstrate that the KHG band aid has very low cytotoxicity.